164k views
5 votes
|2(x - 3) + 5| - 4 = 6x

1 Answer

1 vote

Answer:

I believe the answer is

x=
(7)/(4) or 1.75

Explanation:

l2(x+3)+5l-4=6x

add 4 to each side

l2(x+3)+5l=6x+4

distribute 2 into (x+3)

2x+6+5=6x+4

add same like terms

2x+11=6x+4

subtract 6x on each side

-4x+11=4

subtract 11 on each side

-4x=-7

then, divide -4 on both sides

x=
(7)/(4)

User Jman
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.